Oil-in-water nano-emulsions boost rice innate immune response against Pyricularia oryzae via the induction of salicylic acid-mediated pathway and the enhancement of antioxidant machinery - Zeinab A. Kalboush; Yasser S.A. Mazrou; Amr A. Hassan; Osama Abd El Badeea; Yasser Nehela (Plant Stress)
Rice blast, caused by Pyricularia oryzae, is a challenging disease worldwide. The management of this serious disease mainly depends on chemical fungicides, which negatively affect human health, non-target organisms, and the environment. Therefore, searching for eco-friendly alternatives has become a necessity. Herein, we prepared and characterized three essential oil-based nano-emulsions (EO-NEs) from clove (CO-NE), lemongrass (LO-NE), and pelargonium (PO-NE). The prepared NEs were stabilized and maintained their nano-sized droplet during the emulsification and for more than a week of storage at room temperature. Moreover, Prepared NEs showed acceptable stability when centrifuged at 3500 rpm for 30 min. Our in vitro findings showed that EO-NEs significantly suppressed the spore germination, caused several morphological abnormalities in germ tubes, and inhibited the mycelial growth of P. oryzae in a dose-dependent manner. Moreover, the newly prepared EO-NEs' performance and their bulk emulsions were tested under greenhouse and open-field conditions. EO-NEs suppressed the development of rice blast disease and significantly decreased the leaf and panicle blast severity under both conditions. EO-NEs enhanced the defense responses of rice plants against P. oryzae via the induction of a complex multilayered defense system. The reduced disease severity was associated with activating both enzymatic (peroxidase [POX] and ascorbate peroxidase [APX]) and non-enzymatic (phenolics and flavonoid levels) antioxidant defense machinery. Furthermore, it was also correlated with the induction of the salicylic acid (SA)‐mediated defense pathway (SA content, phenylalanine ammonia-lyase [PAL] activity, and expression of two WRKY transcription factors). Interestingly, EO-NEs slightly enhanced the chlorophyll content and improved the grain yield of P. oryzae-infected rice plants, suggesting no phytotoxicity on treated plants. The findings of this study not only outline the potential application of oil-in-water NEs as sustainable, easy-to-use alternatives against P. oryzae but also decipher the physiological and biochemical mechanisms behind their protective role.